The Case for Government Supported Training Program - Gunderson, Morely (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
Concepts of Public Expenditure Economies are applied to the operation of labour markets in general and training programs in particular to see if the free market provides a socially optimal amount of training. The case for government-supported training is discussed when there exist market imperfections and equity considerations, as well as market failure due to externalitiesyhigh risk and uncertainty, and merit goods.